Recovery From Inner Child - Lies imma Junaidah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The phenomenon of inner child or childhood experiences is one of the factors that shapes a person's character. Everyone experiences their own inner child to varying degrees and with different impacts. Family conflicts experienced during childhood, harsh treatment or words received by parents during childhood can have the impact of painful emotional wounds on a child who becomes an inner child. Parenting style is an important factor in the formation of an inner child. Parenting is the interaction between parents and children, what is the attitude or behavior of parents when interacting with children, for example how to set rules, teach normative values, provide attention and affection and show good attitudes and behavior so that they become role models and role models for children. -his son. The research aims to review one of the factors causing mental health disorders, namely the inner child and how the book of Isa reconciles and escapes the negative influence of the inner child based on research journals that have been conducted previously. The method used in this research is the Literature Review research method.. The result requires self-awareness of the inner child within oneself and this will help to reprogram one's conscious mind to be more adaptable to current life. Try to make peace with the existence of your inner child so you can live a more positive and happy life. This inner child cannot be considered trivial because it can have a negative impact on the person's personality and a solution needs to be found, so that it doesn't happen again in future generations, because if this inner child is not cured it will become a chain of inner children that will continue to repeat itself in the next generation..